2021
DOI: 10.1371/journal.pone.0261472
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Kentucky bluegrass subject to drought and ethephon treatment

Abstract: Kentucky bluegrass (Poa pratensis L.) is an excellent cool-season turfgrass utilized widely in Northern China. However, turf quality of Kentucky bluegrass declines significantly due to drought. Ethephon seeds-soaking treatment has been proved to effectively improve the drought tolerance of Kentucky bluegrass seedlings. In order to investigate the effect of ethephon leaf-spraying method on drought tolerance of Kentucky bluegrass and understand the underlying mechanism, Kentucky bluegrass plants sprayed with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 129 publications
(134 reference statements)
1
7
0
Order By: Relevance
“…Ethephon (150 mg L −1 ) seed treatment increased the antioxidant enzymes' activity, as well as reduced MDA content and electrolyte leakage compared to control (Zhang et al, 2018b). Similarly, Zhang et al (2021b) revealed that seed priming with ethylene (200 mg L −1 ) influenced the expression of genes related to signal transduction pathways, protein denaturation and stabilization, transportation, osmosis, and the antioxidant system in kentucky bluegrass. Exogenously‐applied ethylene at a concentration of 1.0 mM has a beneficial effect on maize under drought stress.…”
Section: Tolerance Mechanisms‐induced By Ethylene Under Drought Stressmentioning
confidence: 92%
See 2 more Smart Citations
“…Ethephon (150 mg L −1 ) seed treatment increased the antioxidant enzymes' activity, as well as reduced MDA content and electrolyte leakage compared to control (Zhang et al, 2018b). Similarly, Zhang et al (2021b) revealed that seed priming with ethylene (200 mg L −1 ) influenced the expression of genes related to signal transduction pathways, protein denaturation and stabilization, transportation, osmosis, and the antioxidant system in kentucky bluegrass. Exogenously‐applied ethylene at a concentration of 1.0 mM has a beneficial effect on maize under drought stress.…”
Section: Tolerance Mechanisms‐induced By Ethylene Under Drought Stressmentioning
confidence: 92%
“…It also facilitates the growth of new adventitious root systems and sustains fundamental metabolism, thereby promoting plant tolerance to drought stress (Zhang et al, 2013). Ethylene acquisition is crucially linked with the varying degrees of drought exposure, which affects every aspect of plant stages (Cui et al, 2015; Zhang et al, 2021b; Chen et al, 2022). Furthermore, increased ethylene production in response to drought stress reduces growth rate, photochemical efficiency, and grain yield by accelerating leaf and flower abscission and senescence (El‐Beltagy & Hall, 1974; Beltrano et al, 1999; Yang et al, 2014a), indicating that ethylene has a biphasic function in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Scarpeci et al (2017) showed that overexpressing AtERF019 in Arabidopsis increased drought tolerance and decreased transpiration rate by reducing stomatal conductance. In a study by Zhang et al (2021), an ethephon (a liquid formulation that releases ethylene gas after spraying) pre‐treatment was administered to Kentucky bluegrass ( Poa pratensis L.), which subsequently led to an osmotic enhancement when exposed to drought stress by promoting antioxidant enzyme activity and the accumulation of proline. Similarly, priming wheat grains with ethylene has been shown to elicit improved drought tolerance by regulating auxin and abscisic acid signaling, ROS scavenging, and osmotic regulation (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some up-regulated DEGs included PYL, JAZ and BSK involved in the hormone signaling transduction of ABA, jasmonic acid (JA) and brassinosteroid (BR) [18]. An RNA-seq approach using three germplasm sources with different drought tolerances identified transcript isoforms exhibiting a shared response of all three germplasm sources to drought stress and transcript isoforms exhibiting a tolerance response, where the more drought-tolerant germplasm sources exhibited higher transcript differences compared to the drought-susceptible cultivar [19].…”
Section: Introductionmentioning
confidence: 99%